ZnO (Ag-N) Nanorods Films Optimized for Photocatalytic Water Purification - Sanchez, Luis (2019)
ZnO nanorods (NRs) films, nitrogen-doped (ZnO:N), and ZnO doped with nitrogen and decorated with silver nanostructures (ZnO:N-Ag) NRs films were vertically supported on undoped and N doped ZnO seed layers by a wet chemical method. The obtained films were characterized structurally by X-ray diffraction. Morphological and elemental analysis was performed by scanning electron microscopy, including an energy dispersive X-ray spectroscopy facility and their optical properties by Ultraviolet-Visible Spectroscopy. Analysis performed in the NRs films showed that the nitrogen content in the seed layer strongly affected their structure and morphology. The mean diameter of ZnO NRs ranged from 70 to 190 nm. As the nitrogen content in the seed layer increased, the mean diameter of ZnO:N NRs increased from 132 to 250 nm and the diameter dispersion decreased. This diameter increase occurs simultaneously with the incorporation of nitrogen into the ZnO crystal lattice and the increase in the volume of the unit cell, calculated using the X-ray diffraction patterns and confirmed by a slight shift in the XRD angle. The diffractograms indicated that the NRs have a hexagonal wurtzite structure, with preferential growth direction along the c axis. The SEM images confirmed the presence of metallic silver in the form of nanoparticles dispersed on the NRs films. Finally, the degradation of methyl orange (MO) in an aqueous solution was studied by UV-vis irradiation of NRs films contained in the bulk of aqueous MO solutions. We found a significant enhancement of the photocatalytic degradation efficiency, with ZnO:N-Ag NRs film being more efficient than ZnO:N NRs film, and the latter better than the ZnO NRs film.